Limitations of economic efficiency as normative criterion: origin and consequences (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
Economic efficiency inspired by the neoclassical economic theory, has become a fundamental valuation approach in making economic, business, political and social decisions. In this paper we suggest some of the philosophical and anthropological keys that have historically inspired its configuration, elements that have accompanied the history of economic thought and prompted the working hypotheses and human models adopted under study. This analysis let us to consider some of its limitations and the consequences arising in the implementation of efficiency as a normative criterion.
Keywords: economic efficiency; economic history; utilitarianism; anthropology; Ethics; moral freedom; thelos; methodological individualism; neoclassical economics; subjective preferences; welfare; altruism; reciprocity.